Potensi Serangan Hama Lalat Buah Bactrocera sp (Diptera: Tephritidae) Pada Beberapa Komoditas Hortikultura di Pasar Rakyat Kota Kefamenanu - Bay, Maria Marselina; Pakaenoni, Gonsianus (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2021)
Fruits and vegetables are examples of commodities that are widely traded in people's markets because they are one of the basic needs of the community. The presence of fruit fly attacks on fruits and vegetables traded in public markets is one of the causes for the low quality of these commodities. Information about fruit fly infestations in horticultural commodities traded in public markets is still limited. The purpose of this study was to obtain information related to the ability of fruit flies to invest in commodities that are traded in the people's markets in the city of Kefamenanu. The research was conducted using a survey method and taking several types of traded commodities, the stages of maintenance and identification were carried out in the Biology Education laboratory of the University of Timor from July 2020 to September 2020. The results showed that there were five species of fruit flies that attacked several types of horticultural commodities traded in public markets, namely Bactrocera dorsalis which attacked cayenne pepper, curly chili, large chili, star fruit, guava and tomato. Bactrocera carambolae attacks star fruit. Bactrocera albistrigata attacks curly peppers, cayenne pepper and guava. While Bactrocera passiflorae attacks guava. From the results of this study, important information was obtained that fruit fly pests not only attack horticultural crops in agricultural areas, but can also attack horticultural commodities that have been harvested and traded in the people's markets in Kefamenanu City.